VERIFICATION OF THE HISAB EPHEMERIS SYSTEM AGAINST THE HIJRI CALENDAR LEAP YEAR PATTERN WITH CRITERIA IMKAN AL-RUKYAH MABIMS (Case Study in Kudus District) - Fika Afhamul Fuscha (Al-Hilal: Journal of Islamic Astronomy, 2021)
The hijri istilahi calendar has a 30-year cycle system, wherein 30 years there are 11 leap years and 19 basithoh years. In history, there are 4 kinds of variants in the placement of the leap year. This research aims to determine the leap year pattern of Kudus district in 30 years and to verify which patterns are close to the 4 kinds of variants. This study uses the Library Research method using a descriptive verification approach. This approach provides a sample of the number of days per month for 30 years using the Ephemeris reckoning system by considering the possibility of seeing the new moon based on the criteria of Imkan al-Rukyah MABIMS. If the hilal meets the MABIMS criteria, then the number of days is 29, but if not, then the number of days will be 30. Then, the number of days each month is accumulated annually and is used to verify the number of days each year on the hijriah istilahi calendar. Based on the analysis of the initial month data at the Kudus district headquarters for a period of 30 years, it turns out that in the period of 1411 H to 1440 H, the spread pattern of leap years is closer to pattern IV. There are 5 years whose leap is the same as the IV pattern, namely 2, 8, 16, 24, and 30.